2021
DOI: 10.1002/ccr3.5039
|View full text |Cite
|
Sign up to set email alerts
|

Molecular hydrogen as an adjuvant therapy may be associated with increased oxygen saturation and improved exercise tolerance in a COVID‐19 patient

Abstract: Administration of molecular hydrogen dissolved in water to patient with COVID‐19‐like symptoms may improve oxygen levels and exercise capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…Furthermore, imbibition of HRW has been demonstrated to improve O2 saturation and fatigue in a case study of post-COVID-19-like syndrome. 91 However, these results were not corroborated in a larger clinically controlled group 92 where almost doubling the concentration and duration of H2 exposure (227mL of HRW, containing 1.6mg/L (0.8mM) of H2, consumed up to five times a day for 28 days) did not produce significant data. In accordance, further in-depth research will be required if accurate dosage and treatment protocols are to be delineated.…”
Section: Molecular Hydrogen (H2) As a Treatment For Post-covid-19 Syn...mentioning
confidence: 89%
“…Furthermore, imbibition of HRW has been demonstrated to improve O2 saturation and fatigue in a case study of post-COVID-19-like syndrome. 91 However, these results were not corroborated in a larger clinically controlled group 92 where almost doubling the concentration and duration of H2 exposure (227mL of HRW, containing 1.6mg/L (0.8mM) of H2, consumed up to five times a day for 28 days) did not produce significant data. In accordance, further in-depth research will be required if accurate dosage and treatment protocols are to be delineated.…”
Section: Molecular Hydrogen (H2) As a Treatment For Post-covid-19 Syn...mentioning
confidence: 89%
“…and this mechanism, generates the superoxide. Molecular hydrogen has been found to be useful in protecting against free radical induced damage due to its potential antioxidant effects in various conditions [20][21][22][23][24][25][26][27][28][29].…”
Section: Free Radical Stress and Antioxidants In The Pathogenesis Of ...mentioning
confidence: 99%
“…Dietary approaches consisting of Mediterranean-style foods, yoghurt, and butter milk are used to alter the composition and improve function of the communities of the microbes that develop colonies in the gut for improvement of health, and protect against CVDs and T2DM [8,9]. In view of the known beneficial effects of hydrogen therapy [20][21][22][23][24][25][26][27][28][29], there is a need to understand how it is produced in the gut. A pilot study reported increased production of intestinal hydrogen along with recovery in muscle function following intensive exercises [30].…”
Section: Production Of Molecular Hydrogen In the Gutmentioning
confidence: 99%
“…Numerous studies have indicated that H 2 has anti-inflammatory [ 22 ], anti-apoptosis [ 23 ], antifatigue [ 24 , 25 , 26 , 27 ], and regulatory properties [ 28 ]. Based on the reported beneficial health effects across a variety of diagnoses [ 22 , 29 ], H 2 administration has recently been proposed as a promising therapeutic gas for COVID-19 patients [ 7 , 30 , 31 , 32 , 33 , 34 , 35 ]. For instance, Guan et al [ 36 ] showed clinically beneficial effects of a hydrogen/oxygen (H 2 –O 2 ; 66–33%) mixed gas inhalation for the amelioration of most respiratory symptoms, such as dyspnea, chest distress, or cough, within days 2 and 3 of hospitalization for COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%